Inhibitory Effect of 5-Aza-2â€™-Deoxytidine on Cell Viability of the Oral Cancer Cell Line, ORL-48T - M.S Rawaidah, N.; S Syairah, N.; H Khor, G.; M. Amin, I.; Harun, N.; Y.P.M. Yusof, M.; R.A Froemming, G. (International Journal of Engineering and Technology, 2018)
Oral cancer is recorded as the sixth highest malignancy globally. 5-Aza-2'-deoxycytidine (5-Aza-dC) has been applied as an inhibitory agent in various tumourous cells. Previous studies showed that 5-Aza-dC can inverse genes silencing resulting from hypermethylation process. Inhibitory effects of 5-Aza-dC on oral cancer cell lines, ORL-48T proliferation was studied using 3-(4,5-dimethylthiazol-2-yl)-2,5 -diphenyltetrazolium bromide (MTT)-based assay in this study. The results demonstrated the treatment with 20 ÂµM 5-Aza-dC for 144 h and 40 ÂµM with 72 h respectively, revealed a significantly decreased percentage of viable tumour cells (p= 0.03). This current study provides an evidence of the inhibitive effect of 5-Aza-dC on the ORL-48T cells proliferation.Â Â